The Total Irregularity Strength of a Comb Product of Stars - Tilukay, Meilin Imelda; Batkunde, Harmanus (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2024)
A totally irregular total k-labeling λ: V U E → 1, 2, ⋯ , k of a graph G is a labeling where the weights of all distinct vertices and edges are unique. The weight w(x) of a vertex x is defined as the sum of its label and the labels of all edges incident to it, while the weight w(e) of an edge e is the sum of its label and the labels of its two endpoints. The minimum k for which G admits such a labeling is known as the total irregularity strength of G, denoted ts(G). This study focuses on determining ts(G) for specific classes of trees, including the comb product of stars, where the contact vertex is the central vertex of one star, and the triple star graph.Keywords: comb product; star; total irregularity strength; totally irregular total labeling graph. AbstrakPelabelan k-total tak teratur total λ: V U E → 1, 2, ⋯ , k dari suatu graf G adalah suatu pelabelan sedemikian sehingga bobot setiap titik dan sisi masing-masing berbeda. Bobot suatu titik w(x) adalah jumlah label titik x dan label setiap sisi yang terkait ke x, dan bobot suatu sisi w(e) adalah jumlah label sisi e dan kedua titik yang terkait ke e. Nilai minimum k sehingga suatu graf G memiliki pelabelan tersesebut dikenal sebagai nilai ketakteraturan total dari G, dinotasikan dengan ts(G). Pada artikel ini, ditentukan nilai ketakteraturan total dari suatu kelas graf pohon, yaitu hasil operasi comb dari graf bintang, dimana titik tetapnya adalah titik pusat graf bintang, dan graf bintang tripel. Kata Kunci: hasil operasi comb; graf bintang, nilai ketakteraturan total; pelabelan total tak teratur total. 2020MSC: 05C78